A DESIGN OF PIEZOELECTRIC VIBRATION ABSORBER WITH THE CAPACITIVE ADJUSTMENT - MAREK PIETRZAKOWSKI (TASK Quarterly, 2002)
In the paper the problem of vibration damping via piezoelectric absorbers capacitively shunted is studied. The considered system is a simply supported beam with the absorber composed of piezoceramic patches joined by means of brackets in a uniform distance from the beam surface, symmetrically on both sides of the beam. Due to the applied damping strategy piezoceramic actuators are shunted with a changeable capacitor in the external circuit to tune the resonance frequencies of the system. The analysis is completed with results of numerical simulations.